STUDY SURVEI RESPON SISWA DALAM PEMBERIAN TUGAS RUMAH (PR) PADA MASA PANDEMI COVID 19 - Riska Melinda; Eliana Yunitha Seran; Fatkhan Amirul Huda (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2020)
The Purpose of this research is for know student responsed in gave homework (PR) during covid 19 pandemic in Sekolah Dasar Negeri 01 Sintang. This research is survey research with quantitative methods approach. Data collect used quesionnare. This research population are 129 students, within sample of this research are 50 students. The result of this research is student responses in gave homework (PR) during covid 19 pandemic in Sekolah Dasar Negeri 01 Sintang academic year 2020/2021 in strange category, next in fill the quesionnare which filled by 50 students from class VA, VB, and VC and reach score 4111 with average 82,22 and persentage quesionnare is 82,22%. The result which influenced students responsed in gave homework (PR) Sekolah Dasar Negeri 01 Sintang academic year 2020/2021 highest 70% from which hoped. Based on calculation given score tcalculated more huge than ttabel score is 22,21>1,67, however H0 rejected  and Ha accepted.